Workshop On Early Detection Overweight In Adolescents At Karuna Dipa Junior High School In Palu City: Workshop Deteksi Dini Kegemukan Pada Remaja Di SMP Karuna Dipa Kota Palu - Wery Aslinda; Ansar Ansar; Bahja Bahja (Poltekkes Kemenkes Palu, 2021)
Indonesia as a developing country is one of the contributors to the increasing incidence of Overweight adolescents. The form of activities such as providing counseling and training on early detection of overweight and providing short workshops on making healthy snacks to prevent obesity (Banana Bud) is one of the efforts to prevent obesity in adolescents. The purpose of this community service is to increase adolescent knowledge about overweight prevention, improve adolescent skills in early detection of overweight and in selecting and making snacks to prevent overweight. This type of community service is providing counseling and training on early detection of overweight as well as providing a short workshop on making healthy snacks to prevent overweight (Banana bud) at Karuna Dipa junior high school in Palu City. Knowledge assessment results show that an increase in the average knowledge score was 2.9 points (14.5%). For the skill of determining BMI, students achieved the ability of 72% which was assessed from their ability to calculate BMI using discs or using a calculator, while for the determination of overweight, students' abilities reached 83% which was assessed from their ability to use discs to detect overweight. The conclusion of community service is that there is an increase in knowledge, skills for determining BMI using discs and calculators, and knowledge of making healthy snacks to prevent overweight